2011
DOI: 10.1177/0020764011406807
|View full text |Cite
|
Sign up to set email alerts
|

The influence of gender role on the prediction of antisocial behaviour and somatization

Abstract: Gender role may be important to the expression of antisocial behaviour, but does not influence somatic symptoms. Current findings underscore the need to consider that observed sex differences in antisocial behaviour might actually be affected by gender role, and highlight the importance of considering societal expectations of male and female behaviour when examining apparent sex differences in behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
1
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 57 publications
3
1
1
7
Order By: Relevance
“…According to gender, findings showed differences in specific personality domains, with females reporting higher Negative affectivity scores and males showing higher Antagonism. These data are consistent with those of a recent study (Romero & Alonso, 2019) and confirmed previous results regarding higher prevalence of antisocial traits among males (Castro, Carbonell & Anestis, 2012) as well as a higher incidence of anxiety and internalizing disorders in females (Kessler, Berglund, Demler, Jin, Merikangas & Walters, 2005). These gender differences are likely to be rooted in biological, cognitive, social‐emotional and cultural factors (Zahn‐Waxler, Shirtcliff & Marceau, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…According to gender, findings showed differences in specific personality domains, with females reporting higher Negative affectivity scores and males showing higher Antagonism. These data are consistent with those of a recent study (Romero & Alonso, 2019) and confirmed previous results regarding higher prevalence of antisocial traits among males (Castro, Carbonell & Anestis, 2012) as well as a higher incidence of anxiety and internalizing disorders in females (Kessler, Berglund, Demler, Jin, Merikangas & Walters, 2005). These gender differences are likely to be rooted in biological, cognitive, social‐emotional and cultural factors (Zahn‐Waxler, Shirtcliff & Marceau, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the findings are congruent with accumulating evidence for the high prevalence of antisocial traits among men (e.g. Castro et al 2012;Hamburger et al 1996) because males were found to score higher than females on antagonism.…”
Section: Discussionsupporting
confidence: 84%
“…Femininity was found to be protective against both a high and increasing symptom severity. This is different from earlier crosssectional studies that showed an association between femininity, measured by the gender index, domestic responsibilities, or the BEM sex role inventory, respectively, and higher levels of common somatic symptoms (Ballering et al, 2020;Krantz & Ostergren, 2001) or that found no association (Castro, Carbonell, & Anestis, 2012). These differences may be explained by the longitudinal nature of the current study, which provides insight into the dynamics of symptoms over time and may result in a more precise assessment of somatic symptom severity.…”
Section: Sex and Gender In Relation To Somatic Symptom Trajectoriescontrasting
confidence: 99%